FAKTOR-FAKTOR YANG MEMPENGHARUI KUNJUNGAN IBU HAMIL PADA TRIMESTER PERTAMA DI PUSKESMAS KAIRATU KABUPATEN SERAM BAGIAN BARAT TAHUN 2013 - Yonce Heumasse (VISIKES: Jurnal Kesehatan Masyarakat, 2019)
ABSTRAK Antenatal health services by pregnant women in the first trimester can make it difficult for health workers to provide comprehensive and comprehensive guidance and maintenance for the health of pregnant women, including early detection of risk factors. This is one of the results of the Maternal Mortality Rate in Indonesia (Peranginangin,2010). The purpose of this study was to obtain information about the factors that influence the visit of pregnant women in the first trimester. The research method used in this research is analytic survey research by studying "Cross Sectional". The samples used in this study were all pregnant women who did not carry out antenatal examinations in the first trimester at the Kairatu Health Center. The technique used was accidental sampling, which is the technique of taking the samples used available or available. Data analysis in qualitative research is in principle an induction process, conceptualization interpretation. The results of the study were obtained from interviews about the phenomenon of pregnant women in conducting antenatal care in the first trimester of pregnant women and midwives in the Kairatu Health Center area, namely pregnant women looking for purposes and considering examinations, pregnant women need financial assistance to conduct examinations, even though mothers Pregnants are aware of the importance of funded examinations, but they still believe in traditional birth attendants because they are easier to achieve. Get help with pregnancy related to antenatal care checks, diseases and complications that can occur during low socioeconomic pregnancies that do not require health facilities by making home visits in areas that are also active in promoting posyandu. Kata Kunci             : pregnant women, Knowledge, Economy,Social Culture